Textiles in motion : dress for dance in the ancient world - Gouy, Audrey (Oxford ; Havertown, PA : Oxbow Books, 2023)
"An innovative series of case studies looking at the significance, meaning and social context of costume and textiles used in dance among a variety of ancient cultures and civilisations"--
1. Practical perspectives on dance and clothing / Elizabeth J.W. Barber -- 2. Dancing in flames: fabulous designs from the desert sands: reconstructing the east Central Asian skirts' construction secret / Ulrike Beck -- 3. The whirling dance of Baukis: reinterpreting our sources / Elena Miramontes Seijas -- 4. Dance and metatheatre in Menander's Theophoroumene / Evangelia Keramari -- 5. The unhellenic attire of choruses as image of the "other" in ancient Greek tragedy / Leonidas Papadopoulos -- 6. The dress of the dancing lares / Alexandra Sofroniew -- 7. Dance and clothing in ancient Egypt: the earliest evidence / Heidi Köpp-Junk -- 8. Soft cloth and sounding jewellery: sound fields of rich women in Eastern Hallstatt culture / Karina Grömer and Beate Maria Pomberger -- 9. Flowing white dresses for dancing initiates in the Mysteries of Eleusis / Aikaterini-Iliana Rassia -- 10. Fashioning sensescapes through ancient Egyptian dance / Jordan Galczynski and Robyn Price -- 11. Dancing around the goddess' dress / Angela Bellia -- 12. "Wearing" tattoos in Ancient Egypt: evidence from Middle Kingdom mummies and feminine figurines / Vittoria Rapisarda -- 13. Egyptologist dancers: re-enacting "ancient Egyptian" dances at the beginning of the 20th century / Gerrit Berenike Heiter.
Includes bibliographical references.
Audrey Gouy is Marie Skłodowska-Curie researcher at the Centre for Textile Research, University of Copenhagen, Denmark.
Print version record.
eBooks on EBSCOhost
Keywords: Textile fabrics, Ancient; Dance costume -- History; Clothing and dress -- History -- To 500.; Dance -- History; Dance -- Social aspects; Danse -- Histoire; Textiles et tissus antiques; Danse -- Aspect social; Costumes de danse -- Histoire; SOCIAL SCIENCE / Archaeology; Clothing and dress; Dance; Dance -- Social aspects; Textile fabrics, Ancient; To 500; History